KETERLIBATAN AYAH DALAM MEMBANGUN KARAKTER RELIGIUS ANAK USIA DINI - Eka Putri, Yuliani (Jurnal I TIBAR, 2022)
Early childhood is often referred to as the golden age or the golden age where the potential, intelligence and basics of a person's behavior are formed at this age range. To support this, parents are the first socialization place for children to learn this. This article is the result of a literature study that aims to find out how the involvement of fathers in building children's religious character. This study examines several reputable research articles both nationally and internationally as well as up-to-date books. Based on the results of the analysis of literature studies, it shows that the involvement of fathers in building children's religious character can be started by forming positive communication patterns with children, exemplary that must be implemented with examples of actions that reflect character values ​​that will be imitated by children, habituation that is carried out repeatedly in daily life, as well as direct interaction, closeness and warmth the child feels safe and comfortable with the father.